Modified stage-gate: a conceptual model of virtual product development process - Ale Ebrahim, N.; Ahmed, S.; Taha , Z. (Academic Journals, 2009)
In today’s dynamic marketplace, manufacturing companies are under strong pressure to introduce new products for long-term survival with their competitors. Nevertheless, every company cannot cope up progressively or immediately with the market requirements due to knowledge dynamics being experienced in the competitive milieu. Increased competition and reduced product life cycles put force upon companies to develop new products faster. In response to these pressing needs, there should be some new approach compatible in flexible circumstances. This paper presents a solution based on the popular Stage-Gate system, which is closely linked with virtual team approach. Virtual teams can provide a platform to advance the knowledge-base in a company and thus to reduce time-to-market. This article introduces conceptual product development architecture under a virtual team umbrella. The paper describes all the major aspects of new product development (NPD), NPD process and its relationship with virtual teams, Stage-Gate system finally presents a modified Stage-Gate system to cope up with the changing needs. It also provides the guidelines for the successful implementation of virtual teams in new product development.